2015
DOI: 10.1016/j.nbd.2015.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Clioquinol rescues Parkinsonism and dementia phenotypes of the tau knockout mouse

Abstract: Iron accumulation and tau protein deposition are pathological features of Alzheimer's (AD) and Parkinson's diseases (PD). Soluble tau protein is lower in affected regions of these diseases, and we previously reported that tau knockout mice display motor and cognitive behavioral abnormities, brain atrophy, neuronal death in substantia nigra, and iron accumulation in the brain that all emerged between 6 and 12 months of age. This argues for a loss of tau function in AD and PD. We also showed that treatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 61 publications
(82 reference statements)
2
62
0
Order By: Relevance
“…8), which is also pathology of AD [28,39]. Lowering brain iron has been shown to reduce memory deficits and neuronal loss in AD animal models and in a clinical trial [11,14,[40][41][42][43]. We recently reported that elevated brain iron, as reflected by elevated cerebrospinal fluid ferritin levels, is associated with accelerated cognitive decline [44], highlighting the role of iron in AD progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8), which is also pathology of AD [28,39]. Lowering brain iron has been shown to reduce memory deficits and neuronal loss in AD animal models and in a clinical trial [11,14,[40][41][42][43]. We recently reported that elevated brain iron, as reflected by elevated cerebrospinal fluid ferritin levels, is associated with accelerated cognitive decline [44], highlighting the role of iron in AD progression.…”
Section: Discussionmentioning
confidence: 99%
“…atrophy [11][12][13], caused by brain iron [11,14]. It is thus unclear how the reduction of tau can both precipitate cognitive decline and protect against Aβ-induced toxicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ancient and antiprotozoal drug clioquinol (vioform, 5-chloro-7-iodo-8-hydroxyquinoline) was shown to prevent MPTP-induced neurotoxicity in mice and reversed the motor deficits in tau KO mice [23,24], and blood-brain barrier-permeable chelators VK28 and M30 prevented the neurotoxicity induced by 6-OHDA and MPTP [25][26][27]. In addition, orally given M30 prevented the loss of tyrosine hydroxylase (TH)-positive neurons and attenuated iron accumulation and microglial activation in…”
Section: Introductionmentioning
confidence: 99%
“…For example, the 8-hydroxyquinoline-derived metal ionophores clioquinol and PBT2 have been demonstrated to traffic copper and zinc into cells, prevent Aβ toxicity in vitro, decrease extracellular Aβ levels in vivo and improve the behavioral phenotype of AD model mice [172][173][174][175]. Clioquinol also effectively restored iron levels and reversed cognitive deficits in tau knockout mice, which develop symptoms consistent with both AD and PD [170,176]. Pyrrolidine dithiocarbamate, another copper ionophore, is similarly protective in the APP/PS1 mouse model of AD [177].…”
Section: • • Treatments For Alzheimer's Diseasementioning
confidence: 99%